Hypertensive Retinopathy Secondary to Anlotinib Treatment - Zhang, Xiaohua; Peng, Li; Xie, Qing; Wu, Qingjing; Sheng, Xia (Frontiers in Pharmacology, 2020)
Purpose: We report a case of a middle-aged woman who developed hypertensive retinopathy following oral administration of Anlotinib. Observations: A 48-year-old woman presented to our hospital with sudden painless loss of vision in both eyes combined with headache, nausea and vomiting following oral administration of Anlotinib. This drug is often used to control cancer progression. Due to the deterioration of her blood pressure, which reached 167/113 mm Hg, Anlotinib was discontinued and the blood pressure was controlled by hypertension medications. This normalized her blood pressure, alleviated headache and restored her vision. She visited our eye department 37 days later for eye check-up. The best-corrected visual acuities was 0.3 in the right eye and 0.4 in the left eye. The fundus examinations revealed a clear boundary of the optic papilla with significant stellate exudation in the macular area. The posterior pole of the retina displayed high hemorrhage, with a cotton-wool spot appearance. Optical coherence tomography (OCT) revealed atrophy in the outer segment of macular area, and hard exudations in retinal layers. Based on these findings, hypertensive retinopathy was diagnosed, as a secondary complication of Anlotinib. Conclusions and significance: Anlotinib can induce hypertensive retinopathy. Patients receiving this drug should be closely monitored for potential complications.